2006
DOI: 10.2478/s11756-006-0189-3
|View full text |Cite
|
Sign up to set email alerts
|

Potential for remediation of water repellent soils by inoculation with wax-degrading bacteria in south-western Australia

Abstract: Water repellency resulting from waxy coatings around soil particles causes significant crop and pasture losses. Bioremediation of these soils using inoculation of wax-degrading bacteria was investigated under field conditions. In a small scale experiment without any additional nutrients or soil conditioners, 2 inoculants (Rhodococcus sp. and Roseomonas sp.) out of 7 resulted in significant improvements in water infiltration. A larger scale experiment had compost and fertiliser applied to support inoculants in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 24 publications
1
28
0
Order By: Relevance
“…In the vast regions of south-eastern Australia which have large areas of infertile soils incapable of retaining water for much of the year, farmers have tried a range of options. A potential biological solution is to increase populations of wax-degrading bacteria that consume hydrophobic compounds (Roper 2006). Tillage of soil is a physical solution as the abrasion of particles by farm implements can remove hydrophobic coatings from soil surfaces (Buczko et al 2006).…”
Section: Amelioration Of Water Repellencymentioning
confidence: 99%
“…In the vast regions of south-eastern Australia which have large areas of infertile soils incapable of retaining water for much of the year, farmers have tried a range of options. A potential biological solution is to increase populations of wax-degrading bacteria that consume hydrophobic compounds (Roper 2006). Tillage of soil is a physical solution as the abrasion of particles by farm implements can remove hydrophobic coatings from soil surfaces (Buczko et al 2006).…”
Section: Amelioration Of Water Repellencymentioning
confidence: 99%
“…and Roseomonas sp. (ROPER 2006). Water repellency (WR) tends to be both spatially and temporally highly variable.…”
mentioning
confidence: 99%
“…Inoculation of selected actinobacteria into water-repellent soils in the laboratory under controlled conditions reduced repellency from severe (MED 2.7) to low (MED 1.0) after 150 days compared with the non-inoculated control, which did not change during the course of the experiment (Roper 2004). In the field, improvements in soil wettability following inoculation were less successful, likely due to competition from natural microflora and adverse environmental conditions (Roper 2006). Field data suggested that enhancing existing populations of wax-degrading actinobacteria was more promising.…”
Section: Microbial Inoculation For Wax Decompositionmentioning
confidence: 98%
“…Farmer observations that lime noticeably improved soil wettability in the south-west region of Western Australia led to experiments in the laboratory and in the field demonstrating that the addition of lime to water-repellent soils reduced repellency by 1-3 MED units (Roper 2005(Roper , 2006. For example, in the laboratory under controlled moisture and temperature conditions, treatment of very severely repellent (MED 4.0) soil with lime resulted in significant improvements in wettability (to MED <1.0) over 150 days.…”
Section: Enhancing Existing Populations Of Wax-degrading Bacteria In mentioning
confidence: 99%